Give that g(m) varies inversely with m
So that means we can write equation:
[tex]g\left(m\right)=\frac{k}{m}[/tex]
where is k is constant of variation.
Given that g(m)=3.5 when m=10.
so plug these values into above formula:
[tex]g\left(10\right)=\frac{k}{10}[/tex]
[tex]3.5=\frac{k}{10}[/tex]
[tex]3.5*10=\frac{k}{10}*10[/tex]
[tex]35=k[/tex]
To find the value of m when g(m)=10, we just need to plug g(m)=10 and k=35 into above formula then solve for m
[tex]g\left(m\right)=\frac{k}{m}[/tex]
[tex]10=\frac{35}{m}[/tex]
[tex]10m=35[/tex]
[tex]m=\frac{35}{10}[/tex]
m=3.5
Hence final answer is m=3.5